Implementation of Transformational Leadership to Development Organization and World Class University Strategic (Literature Review) - Primadi Candra Susanto; Tri Widyastuti; Bambang Karsono; Josua Panatap Soehaditama (International Journal of Business and Applied Economics, 2023)
The research methodology used was qualitative using variable-relevant journal mini-reviews of papers and will be completed later in this study. The results of research on various scientific articles, with organizational development in the university environment, also by strengthening with research results from existing scientific articles, the implementation of transformational leadership leadership style is proven in literature studies as well as organizational development for world campuses universities that have been described and answers from scientific article literature studies prove and researchers want to strengthen  The results of research that have been carried out. The recommendation is general because the object here has not yet been determined by the name of the campus and only describes the results of existing research, and can also make further research by other researchers in the future.